ANALISIS PERAN KANTOR URUSAN AGAMA DALAM PENANGANAN KASUS PASANGAN NIKAH SIRI - Muhammad Khusni Mubarok; Eny Shofiawanti; Meilan Arsanti (Islamic Civil Law Departement of Shari'a Faculty at Islamic State University of Sultan Maulana Hasanuddin Banten, 2023)
The purpose of this study was to identify and examine the function of the religious affairs office in handling unregistered marriages in Bonang District. Interviews, observations, and documentation were used in this study. This research is a descriptive qualitative research. Qualitative descriptive analysis techniques emphasize empirical studies that aim to obtain legal information by going directly to the regions. The type of data used in this research is primary and secondary data. The results showed that the role of the religious affairs office in tackling unregistered marriages in Bonang District included providing counseling on registration of marriages and happy families to prospective brides and guardians, conducting socialization on the impact of unregistered marriages, and also the importance of registering marriages every time in filling out a events, both recitations and events involving the head of the religious affairs office. Factors that impede the religious service in handling unregistered marriages in Bonang District include incompetent human resources, low public awareness of law, and inadequate facilities and infrastructure.